2019
DOI: 10.1016/j.jaci.2018.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory checkpoint receptors control CD8+ resident memory T cells to prevent skin allergy

Abstract: Background: Tissue-resident memory T (Trm) cells are detrimental in patients with numerous chronic inflammatory diseases, including allergic contact dermatitis (ACD).Objectives: We sought to analyze the contribution of Trm cells to the chronicity and severity of ACD and to define the local parameters regulating their development and functions. Methods: We used an experimental model of ACD (ie, contact hypersensitivity to 2,4-dinitrofluorobenzene) that is mediated by CD8 1 T cells. Results: Our data show that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 63 publications
5
84
0
2
Order By: Relevance
“…Previous case reports have noted an absence of circulating drug-reactive T cells in severe T cellmediated cutaneous reactions (Iriki et al, 2014), raising the possibility that skin-resident T RM cells are key mediators of such skin hypersensitivity reactions. Moreover, recent work has shown that a reduction in T RM cell function after immune checkpoint blockade therapy may reduce the severity of the nondrug hypersensitivity disease allergic contact dermatitis (Gamradt et al, 2019). Here, our findings show that the skin T cells persist and convert to the T RM cell phenotype following intradermal drug challenge, supporting the hypothesis that skin T RM cells may contribute to cutaneous drug hypersensitivity.…”
supporting
confidence: 85%
“…Previous case reports have noted an absence of circulating drug-reactive T cells in severe T cellmediated cutaneous reactions (Iriki et al, 2014), raising the possibility that skin-resident T RM cells are key mediators of such skin hypersensitivity reactions. Moreover, recent work has shown that a reduction in T RM cell function after immune checkpoint blockade therapy may reduce the severity of the nondrug hypersensitivity disease allergic contact dermatitis (Gamradt et al, 2019). Here, our findings show that the skin T cells persist and convert to the T RM cell phenotype following intradermal drug challenge, supporting the hypothesis that skin T RM cells may contribute to cutaneous drug hypersensitivity.…”
supporting
confidence: 85%
“…A recent study in a mouse model revealed that PD-1 and TIM-3 blockade worsened skin inflammation caused by T RM . 108 The interaction of T RM with radiotherapy alone is less well-understood, and most studies combined radiotherapy with other therapies. In a preclinical study of cervical cancer, the combination of a cancer vaccine (HPV E6/E7) with local X-ray radiation increased the number of intratumoral CD103 + CD8 + T cells and was also associated with increased treatment efficacy.…”
Section: Tissue-resident Memory Cells In the Context Of Immune Checkpmentioning
confidence: 99%
“…In recent years, contact allergy has been used to explore how Toll‐like receptors, the inflammasome and endogenous danger signals impact on the hapten specific CD8 + T‐cell response and skin inflammation . Most recently, Gamradt et al discovered that intrinsic control mechanisms such as immune regulatory (PD‐1 and TIM‐3) signalling determine whether the cytotoxic CD8 + T cells will be reactivated and hence prevent tissue injury. Blocking of immune checkpoints in vivo leads to severe contact hypersensitivity responses with low hapten doses.…”
Section: Immune Checkpointsmentioning
confidence: 99%